(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Indian democracy is implemented in the world’s biggest democracy, yet "Democracy without Justice is Demon-crazy." As we debate the existence of life beyond death, may we introduce another subject for consideration? Does life exist after democracy? What kind of life will it be? When I say "democracy," I am not referring to democracy as an ideal or a goal. Is there life after democracy in the working model? Whether emerging cultures should strive to democracy as an ideal is a distinct topic. I believe it should. The first, idealistic stage may be rather exhilarating. This subject pertains to those living in democracies or nations that claim to be democracies. It does not imply that we should revert to outdated, outmoded types of totalitarian or authoritarian administration. The main aim of the study is to understand the concept and Idea of Justice in the novels of Arundhati Roy and Pankaj Mishra and evaluate democratic practices and Justice in the novels of Arundhati Roy and Pankaj Mishra and compare the writings style and genre of Arundhati Roy and Pankaj Mishra.